Optical detection of bond-dependent and frustrated spin in the two-dimensional cobalt-based honeycomb antiferromagnet Cu3Co2SbO6 - Baekjune Kang; Uksam Choi; Taek Sun Jung; Seunghyeon Noh; Gye-Hyeon Kim; Uihyeon Seo; Miju Park; Jin-Hyun Choi; Min Jae Kim; GwangCheol Ji; Sehwan Song; Hyesung Jo; et al. (Nature Communications)
Abstract Two-dimensional honeycomb antiferromagnets are promising materials class for realizing Kitaev quantum spin liquids. The signature of these materials includes anisotropic bond-dependent magnetic responses and persistent fluctuations in paramagnetic regime. Here, we propose Cu3Co2SbO6 heterostructures as an intriguing candidate, wherein bond-dependent and frustrated spins interact with optical excitons. First-principles spin Hamiltonian calculations and in-plane anisotropic critical fields suggest strong frustration and dominant Kitaev exchange interactions. Optical spectroscopy reveals exciton coupled to frustrated magnetism, enabling optical detection of spin states. Spin-exciton coupling displays anisotropic responses to light polarization along the bond-parallel and the bond-perpendicular directions, highlighting Kitaev interactions and persistent short-range spin correlations above twice the Néel temperatures. The robustness of short-range spin fluctuations under magnetic fields underscores the stability of the spin-fluctuation region. Our results establish Cu3Co2SbO6 as an attractive candidate for exploring quantum spin liquid, where the spin Hamiltonian and quasiparticle excitations can be probed and potentially controlled by light.